Exploring the COVID-19 Pandemic's Impact on the Health Technology Assessment Process of the National Commission for the Incorporation of Technologies Into the Brazilian Health System - Cardoso, Marilia Mastrocolla de Almeida [UNESP]; Thabane, Lehana [UNESP]; Andrade, Luis Gustavo Modelli de [UNESP]; Curado, Daniel da Silva Pereira; Komoda, Denis Satoshi; Rugolo, Juliana Machado; Lima, Silvana Andrea Molina [UNESP]; Weber, Silke Anna Theresa [UNESP] (Elsevier, 2023)
Objectives: This study aimed to evaluate the impact of the COVID-19 pandemic on Brazilian health technology assessment processes based on public reports from the National Committee for Health Technology Incorporation (CONITEC). Methods: This descriptive study analyzed CONITEC's official reports on Brazil available on its website between 2018 and 2021 that aimed to propose recommendations for technologies to be incorporated into its public healthcare system. We used descriptive statistics covering the number of technologies and number of reports about drugs per year, objective, type of technology, demanding sector, and outcome before 2018 to 2019 and during the COVID-19 pandemic (2020-2021). Furthermore, we used logistic regression to explore any association between the final decision labeled as “incorporated” and the emergence of the COVID-19 pandemic. Results: A total of 278 reports were analyzed. Approximately 85% (136 of 278), 79% (220 of 278), and 45% of the reports (125 of 278) were about drugs, for incorporation, and requested by the government, respectively. Moreover, 74 of 130 (57%) and 56 of 148 decisions (38%) were “incorporated” before and during the pandemic, respectively. No significant association was noted between incorporated decisions and the arrival of the COVID-19 pandemic for all technologies (odds ratio 1.43; 95% CI 0.84-2.46; P = .192) and for drugs (odds ratio 1.43; 95% confidence interval 0.81-2.53; P = .223) while adjusting for the type of technology and demandant. Conclusions: The COVID-19 pandemic has brought many challenges, but it does not seem to have had a significant impact on the health technology assessment approval decisions of CONITEC in Brazil.
Keywords: Brazil; COVID-19; health technology assessment; National Committee for Health Technology Incorporation